Design and analysis on different functions of battery energy storage system for thermal power units frequency regulation. (November 2022) - Wang, Qingsong; Yang, Pengfei; Buja, Giuseppe
Abstract: Currently, as more and more new energy sources are connected to the power grid, the pressure on the frequency regulation (FR) of thermal power units (TPU) is increasing. The battery energy storage system (BESS) is used in the scene of auxiliary TPU-FR with its rapid response and accuracy, which has attracted many scholars to study it. However, most scholars only studied the system under normal operating conditions, and did not involve too much on the operating strategy of the system in the event of a failure. In this article, a simulation model of energy storage battery auxiliary FR is built in MATLAB/Simulink, which not only analyzes the response characteristics of the system during normal operation, but also verifies the operation strategy of the system during faults. It is revealed that the existence of energy storage battery reduces the grid frequency offset by 38.1% and increases the power response speed by at least 25 times at normal operation. In addition, the total harmonic distortion of grid-connected voltage and current are 2.54% and 1.72%, respectively, which implies high power quality. When a fault occurs, the energy storage battery is protected by reasonably connecting or removing the BESS based on certain boundary conditions to prolong its life and reduce equipment maintenance costs.